2017
DOI: 10.1016/j.jval.2017.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics, Skeletal Related Events (SRE) And Renal Impairment (RI) In Patients With Multiple Myeloma (MM): A Patient Chart Audit In EU5

Abstract: A413BRAF. There were no studies reporting ethnicity, comorbidities, or incidence of BRAFV600-mutated MM. ConClusions: Our finding that the BRAFV600 prevalence is around 50% is concordant with the literature. Our results also suggest that as much as one-third of MM is V600E-mutated, with the mutation more common in younger patients. However, real-world epidemiological evidence on incidence, comorbidities and toxicity associated with BRAF-mutated MM is still limited, despite the potentially large patient populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A population-based study from the United Kingdom found a 32% rate of SREs among patients with MM who were newly diagnosed between 2004 and 2009 [30]. A 2016 chart audit of medical records of patients with newly diagnosed MM from France, Germany, Italy, Spain, and the United Kingdom found that 26% of patients had ≥1 new SRE between diagnosis and disease progression [31]. An analysis of the Truven Health MarketScan Commercial Claims and Medicare Supplemental databases found that 58% of United States patients with MM diagnosed between 2005 and 2011 experienced an SRE during the follow-up period [14].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study from the United Kingdom found a 32% rate of SREs among patients with MM who were newly diagnosed between 2004 and 2009 [30]. A 2016 chart audit of medical records of patients with newly diagnosed MM from France, Germany, Italy, Spain, and the United Kingdom found that 26% of patients had ≥1 new SRE between diagnosis and disease progression [31]. An analysis of the Truven Health MarketScan Commercial Claims and Medicare Supplemental databases found that 58% of United States patients with MM diagnosed between 2005 and 2011 experienced an SRE during the follow-up period [14].…”
Section: Discussionmentioning
confidence: 99%
“…The data sets generated and analysed during the current study are not publicly available, but they are available from the corresponding author on reasonable request. This study has been previously published as an abstract [51].…”
Section: Fundingmentioning
confidence: 99%